(untitled) (Journal of Engineering, 2024)
Universities are among spaces where it’s important to ensure thermal comfort in indoor spaces, improving the occupants’ well-being and productivity. The problem of the research was to study appropriate glazing systems for the spaces of the University of Baghdad because glazing systems are one of the most important elements of the indoor environments, and it has a major impact on the thermal performance of buildings. Glass is one of the most seasoned materials that are most utilized in the design. Since it is a diaphanous material, it allows sunlight to enter the building, increasing the space’s temperature, cooling loads, and energy consumption in summer. The research followed the experimental method by studying and testing(conventional, advanced, and photovoltaic glazing)by Revit and Onyx Solar analysis in the Architectural Department classes to find the appropriate type of glazing in the spaces of hot, dry areas. The results showed that advanced glazing is the best by reducing the cooling loads andincreasingthermal performance quality. Photovoltaic glazing showed its efficiency in filling part of the electrical energy needs within the spaces of the Architectural department.